237 In vitro potency assays for immune checkpoint blockade using human primary cells, murine huGEMM immune cells and patient-derived tumor organoids. (9th November 2020) - Yan, Xuefei; Zhang, Hongjuan; Zhou, Jun; Zheng, Jia; Zhu, Shuang; Zhang, Rui; Zang, Mingfa; An, Annie Xiaoyu; Xu, Xiaoxi; Wang, Shuzong; Xu, Kevin Qijin; Ouang, Davy Xuesong; et al.
Abstract : Background: The demand of evaluating potency of immune checkpoint modulators is steadily growing for immune-oncology drug development. Methods: We aimed to establish a platform to assess the effects of immune checkpoint blockade using human primary immune cells, humanized murine primary immune cells, and co-cultures of tumor cells or patient-derived tumor organoids with immune cells. Results: First, we validated the potency of immune checkpoint blockade, such as anti-PD-1 antibodies, using mixed lymphocyte reaction (MLR) assay and T cell activation assay by in vitro stimulation. Secondly, we introduced tumor cell lines into co-culture system with immune cells and validate the potency assay by measuring cytokine production and tumor cell killing by allogenic T cells. Thirdly we used huGEMM mouse-derived immune cells to replace human primary immune cells in potency assays. HuGEMM mice express engineered human immune checkpoint targets on immune cells and they can serve as an excellent resource of primary immune cells to test the drug candidates targeting human checkpoints in vitro. Last, we developed a patient-derived tumor organoid co-culture system with immune cells. We profiled the expression of immune inhibitory molecules on the tumor organoids and assessed the potency of immune checkpoint inhibitors. Conclusions: In summary, we have established an extensive in vitro platform to evaluate the potency of the next generation of immune checkpoint inhibitors.